Novel transcriptional regulators of neuroblast self-renewal in Drosophila larval brains - Wong, Melissa Xin Yu (2018)
Mechanisms of self-renewal in neural stem cells are conserved across organisms and are crucial in understanding cancer biology. Type II neural stem cells in Drosophila (neuroblasts) are akin to mammalian stem cells in many ways and are thus a popular model for studying these processes. In this report, we describe a genetic screen to isolate transcriptional regulators interacting with hyrax, a component of the PAF1C complex – a pleiotropic regulator which was recently discovered to influence neuroblast self-renewal. Our study identified 6 novel transcriptional regulators which may interact with hyrax. These results provide a starting point in studying neuroblast morphogenesis, allowing us to further construct the complexed network controlling stem cell self-renewal. As many of these mechanisms are highly conserved, Drosophila neuroblasts can serve as an instructive model for the self-renewal machinery in mammalian neural progenitors.